2011
DOI: 10.1111/j.1748-1716.2010.02237.x
|View full text |Cite
|
Sign up to set email alerts
|

Obesity, insulin resistance and diabetes: sex differences and role of oestrogen receptors

Abstract: Obesity increases the risk of coronary artery disease through insulin resistance, diabetes, arterial hypertension, and dyslipidemia. The prevalence of obesity has increased worldwide and is particularly high among middle-aged women and men. After menopause, women are at an increased risk to develop visceral obesity due to the loss of endogenous ovarian hormone production. Effects of estrogens are classically mediated by the two nuclear estrogen receptors (ERs) α and β. In addition, more recent research has sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
222
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 268 publications
(237 citation statements)
references
References 130 publications
6
222
0
4
Order By: Relevance
“…The increased prevalence of obesity, insulin resistance, and diabetes after menopause reveals a strong influence of E2 on energy balance and glucose homeostasis (Meyer et al, 2011a;Mauvais-Jarvis et al, 2013;Rettberg et al, 2014). Although roles for the classic ERs are well documented in these conditions (Faulds et al, 2012), GPER knockout mice also exhibit insulin resistance, glucose intolerance, dyslipidemia, obesity, and an elevation of proinflammatory cytokines with reduced adiponectin levels (Martensson et al, 2009;Sharma et al, 2013;Davis et al, 2014), despite displaying no differences in food intake or locomotor activity (Sharma et al, 2013;Davis et al, 2014).…”
Section: B Endocrine/neuroendocrine Systemmentioning
confidence: 99%
“…The increased prevalence of obesity, insulin resistance, and diabetes after menopause reveals a strong influence of E2 on energy balance and glucose homeostasis (Meyer et al, 2011a;Mauvais-Jarvis et al, 2013;Rettberg et al, 2014). Although roles for the classic ERs are well documented in these conditions (Faulds et al, 2012), GPER knockout mice also exhibit insulin resistance, glucose intolerance, dyslipidemia, obesity, and an elevation of proinflammatory cytokines with reduced adiponectin levels (Martensson et al, 2009;Sharma et al, 2013;Davis et al, 2014), despite displaying no differences in food intake or locomotor activity (Sharma et al, 2013;Davis et al, 2014).…”
Section: B Endocrine/neuroendocrine Systemmentioning
confidence: 99%
“…Men and women differ in body composition, patterns of weight gain, hormone biology, metabolic markers and the manner in which social, ethnic and environmental factors contribute to the obesity phenotype [24][25][26]. In this context, our observation of a sexually dimorphic association of a polymorphism in the RGS9 gene is significant as it is one of few studies that have demonstrated sex-specific effects of weightinfluencing gene variants.…”
Section: Discussionmentioning
confidence: 66%
“…The severity of abdominal obesity, especially in women, is one of the key factors in the pathogenesis of obesity-related disorders including diabetes, metabolic syndrome, and CVD (31)(32)(33)(34)(35)(36)(37). Therefore, to reduce the risk of cardiovascular events, central obesity should be prevented or stopped (38).…”
Section: Obesity and Cardiovascular Diseasesmentioning
confidence: 99%